The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.31083/j.fbl2801010
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake, Metabolism and Sensing of Long-Chain Fatty Acids

Abstract: Fatty acids (FAs) are critical nutrients that regulate an organism's health and development in mammal. Long-chain fatty acids (LCFAs) can be divided into saturated and unsaturated fatty acids, depending on whether the carbon chain contains at least 1 double bond. The fatty acids that are required for humans and animals are obtained primarily from dietary sources, and LCFAs are absorbed from outside of cells in mammals. LCFAs enter cells through several mechanisms, including passive diffusion and protein-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…Our study provides new insights into the beneficial effects of SGLT2 inhibition in diabetic kidney disease. (32,33) and fatty acid oxidation (34,35). Created with BioRender.com.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides new insights into the beneficial effects of SGLT2 inhibition in diabetic kidney disease. (32,33) and fatty acid oxidation (34,35). Created with BioRender.com.…”
Section: Discussionmentioning
confidence: 99%
“…Transporters involved in cardiomyocyte FA uptake include FA translocase (FAT/CD36), FA binding protein (FABPpm), and FA transport protein (FATP) ( 42 ). FABPpm works with CD36 to facilitate FA transmembrane transport of FAs ( 34 ).…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…Numerous studies have shown that the upregulation of FAS synthesis is a typical metabolic alteration in cancer, which is achieved by the upregulation of transporter proteins and various lipogenic enzymes 40,42–44 . Mammals produce only certain FASs and other FASs notably polyunsaturated FASs, are acquired from the diet by FAS protein transporters (e.g., CD36, SLC27, and plasma membrane FAS‐binding proteins [FASBPs]) 45,46 . Hydrogen sulfide, palmitic acid, and high‐FAst diet‐induced CD36 expression, which enhanced FAS uptake and cancer development 46–49 .…”
Section: Metabolism In Tumorsmentioning
confidence: 99%
“…40,[42][43][44] Mammals produce only certain FASs and other FASs notably polyunsaturated FASs, are acquired from the diet by FAS protein transporters (e.g., CD36, SLC27, and plasma membrane FAS-binding proteins [FASBPs]). 45,46 Hydrogen sulfide, palmitic acid, and high-FAst diet-induced CD36 expression, which enhanced FAS uptake and cancer development. [46][47][48][49] ATPcitrate lyase (ACLY), catalyzes the conversion of citrate and CoA to oxaloacetate and acetyl-CoA, is transcriptionally upregulated by sterol regulatory element binding protein 1 (SREBP1).…”
Section: Lipid Metabolism In Tumorsmentioning
confidence: 99%